2022
DOI: 10.1155/2022/2466789
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Impairment in Cardiopulmonary Exercise Capacity Testing in Patients after COVID-19: A Single Center Experience

Abstract: Background. Following COVID-19, patients often present with ongoing symptoms comparable to chronic fatigue and subjective deterioration of exercise capacity (EC), which has been recently described as postacute COVID-19 syndrome. Objective. To objectify the reduced EC after COVID-19 and to evaluate for pathologic limitations. Methods. Thirty patients with subjective limitation of EC performed cardiopulmonary exercise testing (CPET). If objectively limited in EC or deteriorated in oxygen pulse, we offered cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 57 publications
(51 reference statements)
1
23
0
1
Order By: Relevance
“…30,33 Five studies reported chronotropic incompetence to be a major cause of reduced exercise capacity, 25,30,44,63,64 and most studies reported a lower peak heart rate among individuals with reduced exercise capacity. One study each specifically reported pulmonary fibrosis, 65 pulmonary vascular limitation, 66 impaired microcirculation, 61 endothelial dysfunction, 67 dysautonomia, 64 and loss of mechanical efficiency 28 as the primary etiology of reduced exercise capacity. Despite concerns about pulmonary thromboembolism during acute infection, pulmonary vascular limitations were uncommon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30,33 Five studies reported chronotropic incompetence to be a major cause of reduced exercise capacity, 25,30,44,63,64 and most studies reported a lower peak heart rate among individuals with reduced exercise capacity. One study each specifically reported pulmonary fibrosis, 65 pulmonary vascular limitation, 66 impaired microcirculation, 61 endothelial dysfunction, 67 dysautonomia, 64 and loss of mechanical efficiency 28 as the primary etiology of reduced exercise capacity. Despite concerns about pulmonary thromboembolism during acute infection, pulmonary vascular limitations were uncommon.…”
Section: Resultsmentioning
confidence: 99%
“…29 Evers found no significant changes in peak VO2 over 3 months among 23 individuals with reduced exercise capacity who underwent repeat CPET. 61 Moulson found that peak VO2 improved among young symptomatic athletes 5 months after index study. 32 Improvement correlated with symptom resolution, but peak heart rate was unexpectedly reduced.…”
Section: Longitudinal Trendsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this case, the participant already has objective findings (reduced peak VO2 and chronotropic incompetence) consistent with PASC, which may contribute to reduced exercise capacity and have been shown to persist in some cases. [5][6][7] This suggests that although a short course of early antiviral therapy is adequate to prevent severe acute disease in high-risk patients, [8] it may be insufficient to prevent the development of Long COVID, and those experiencing rebound symptoms could remain at risk. A related hypothesis is that SARS-CoV-2 may persist for weeks to months in some individuals, causing inflammation, local tissue damage, and end-organ disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible to have a reduced exercise capacity as part of “Long COVID” even in the presence of a completely normal cardiac workup. 26 …”
Section: Introductionmentioning
confidence: 99%